Analysis of microstructural, thermal and mechanical properties of unidirectional glass fiber fabrics exhibiting sizing migration. (1st May 2019) - Harinath, P.N.V.; Radadia, Nishil; Bramhe, Sachin; Surendran, Deepu; Sabane, Vinayak; Singh, Alok; Kim, Taik Nam; Sharbidre, Rakesh; Cheol, Byen Ji; Peters, Luc; Bersee, Harald; Nanda, Hitesh; et al.
Abstract: Glass fibre/epoxy composites are widely used in construction, aerospace, automotive and wind turbine industries. During the manufacturing of glass fibres, they are surface-treated with an aqueous polymeric solution in a process called as sizing. This aqueous sizing composition protects the fibers, eases its handling and facilitates the interaction of fibres and matrix at the interface which affects the mechanical properties of the composites. The present study looks at the effect of a phenomenon called as 'sizing migration' on the strength, stiffness and failure mechanisms under tensile, compressive and inter-laminar shear loads in unidirectional glass fiber/epoxy composites. A detailed study has been performed to elucidate how sizing morphology underlying these glass fibers impact the stress-strain behaviour of the composite. Unidirectional glass fiber/epoxy composites were manufactured using vacuum assisted resin infusion molding process which exhibited a fiber volume fraction of ∼58 ± 2%. From the analysis of the relevant mechanical parameters, an intrinsic correlation between the strength and the sizing migration phenomenon has been deduced and explained on the basis of stress-strain curves under different loading conditions. The present study can help in defining the acceptance and rejection criteria in unidirectional fabrics with sizing migration issues.